Building a living economy through modern information decision support systems and UN sustainable development goals. Issue 11 (9th September 2020) - Modgil, Sachin; Gupta, Shivam; Bhushan, Bharat
Abstract: The sustainable development goals (SDGs) set up by the United Nations in 2015 has mounted significant pressure on world economies and business organizations to achieve them by 2030. We operationalized a case using modern information decision support systems (MIDSS) as a fundamental and supportive mechanism utilizing the shared vision across the value chain of an ecosystem to realize the SDGs. Stakeholder theory has been used to argue that shared and cooperative vision can only enable the entire ecosystem to move towards the identified SDGs for living economy and measure the change over a period. We bid for a framework highlighting the role of MIDSS as enablers for achieving the SDGs in stipulated time. The framework is developed based on thematic classification of the data collected by conducting the 31 semi-structured interviews with key people from the industry through 11 questions. We contend that shared vision and trust focussed on stakeholder view linked with common objective of the value chain can create a baseline to hit the target of SDGs around economic, ecological and societal benefits. The framework is useful for the working executives as it can act as reference plug to support and align the organizational activities towards SDGs.